2018
DOI: 10.1002/ece3.3957
|View full text |Cite
|
Sign up to set email alerts
|

Effects of female preference intensity on the permissiveness of sexual trait polymorphisms

Abstract: Recent developments in sexual selection theory suggest that on their own, mate preferences can promote the maintenance of sexual trait diversity. However, how mate preferences constrain the permissiveness of sexual trait diversity in different environmental regimes remains an open question. Here, we examine how a range of mate choice parameters affect the permissiveness of sexual trait polymorphism under several selection regimes. We use the null model of sexual selection and show that environments with strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 38 publications
(69 reference statements)
0
10
0
Order By: Relevance
“…For a combination of PFD strength ( β ) and mate preferences ( α 1 and α 2 ), joint trait‐preference starting frequencies that will maintain polymorphism in T at equilibrium form a zone in the trait‐preference frequency space (Figure 1b). Following Ponkshe and Endler (Ponkshe & Endler, 2018, 2019), we refer this zone as polymorphic zone. The polymorphic zone has two distinct boundaries.…”
Section: Model and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For a combination of PFD strength ( β ) and mate preferences ( α 1 and α 2 ), joint trait‐preference starting frequencies that will maintain polymorphism in T at equilibrium form a zone in the trait‐preference frequency space (Figure 1b). Following Ponkshe and Endler (Ponkshe & Endler, 2018, 2019), we refer this zone as polymorphic zone. The polymorphic zone has two distinct boundaries.…”
Section: Model and Resultsmentioning
confidence: 99%
“…Variable Strawberry poison‐dart frog ( Oophaga pumilio ) is an iconic example of such interaction where both males and females express warning colors and females use visual cues during mate choice (Maan & Cummings, 2008; Siddiqi et al, 2004; Summers et al, 1999) and prefer matching males over non‐matching males (Reynolds & Fitzpatrick, 2007). Recent developments in sexual selection theory suggest that on their own, mate preferences can promote the maintenance of sexual trait diversity (M'Gonigle et al, 2012; Ponkshe & Endler, 2018; Servedio & Bürger, 2014). However, how mate preferences contribute to the maintenance of polymorphism in PFD‐affected sexual traits is largely neglected.…”
Section: Introductionmentioning
confidence: 99%
“…Costly female preferences for local male displays could then be maintained by recurring immigration (Day 2000; Proulx 2001; Reinhold 2004). This mechanism could be commonplace if mating preferences and resulting sexual selection vary spatially (Payne and Krakauer 1997; Day 2000; Brooks 2002; Kingston et al 2003; Chunco et al 2007; Gray and McKinnon 2007; M’Gonigle et al 2012; Wellenreuther et al 2014; Ponkshe and Endler 2018; Dytham and Thom 2020). Indeed, several models have shown that evolution of divergent female preferences can cause spatially variable sexual selection, for example given spatially varying natural selection on male display (Lande 1982; Day 2000), varying male dispersal depending on mating success (Payne and Krakauer 1997) and spatial variation in carrying capacity combined with mate-search costs in females (M’Gonigle et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…2012; Wellenreuther et al. 2014; Ponkshe and Endler 2018; Dytham and Thom 2020). Indeed, several models have shown that evolution of divergent female preferences can cause spatially variable sexual selection, for example, given spatially varying natural selection on male display (Lande 1982; Day 2000), varying male dispersal depending on mating success (Payne and Krakauer 1997), and spatial variation in carrying capacity combined with mate‐search costs in females (M'Gonigle et al.…”
mentioning
confidence: 99%
“…Costly female preferences for local male displays could then be maintained by recurring immigration (Day 2000;Proulx 2001;Reinhold 2004). This mechanism could be commonplace if mating preferences and resulting sexual selection vary spatially (Payne and Krakauer 1997;Day 2000;Brooks 2002;Kingston et al 2003;Chunco et al 2007;Gray and McKinnon 2007;M'Gonigle et al 2012;Wellenreuther et al 2014;Ponkshe and Endler 2018;Dytham and Thom 2020). Indeed, several models have shown that evolution of divergent female preferences can cause spatially variable sexual selection, for example, given spatially varying natural selection on male display (Lande 1982;Day 2000), varying male dispersal depending on mating success (Payne and Krakauer 1997), and spatial variation in carrying capacity combined with mate-search costs in females (M'Gonigle et al 2012).…”
mentioning
confidence: 99%